MODERN DATA ON THE ORIGIN OF MONOTREMES (MAMMALIA) - Tatarinov L.P. (My University, 2001)
Monotremes developed a middle ear containing three auditory ossicles and a modified mandibular depressor independently of therian mammals. This suggests that the similarity between the most primitive therians and the Lower Cretaceous monotreme Steropodon may be convergent. In contrast to the inner ear of therians, that of monotremes retains the macula lagenae characteristic of reptiles and lower vertebrates. In various mammalian lineages, the cochlea lengthened as a result of parallel development; monotremes lack a true Corti's organ. The roots of monotremes are in the most primitive docodonts or, most probably, in primitive triconodonts from the Upper Triassic and Lower Jurassic.
Keywords: Monotremes; Cretaceous; Мезозой::Меловая; Mesozoic::Cretaceous